Peran Moderasi Partisipasi Masyarakat Pada Pengaruh Kompetensi Pengelola, Sistem Pengendalian Internal Dan Pemanfaatan Teknologi Informasi Terhadap Akuntabilitas Pengelolaan Dana Kampung - Eva Warninda; Otniel Safkaur; Dhyta M Nababan (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2025)
This study analyzes the influence of managerial competence, internal control systems, and the utilization of information technology on the accountability of village fund management, as well as the moderating role of community participation in Arso Barat District, Keerom Regency. The research used a quantitative approach with a survey method, distributing questionnaires to 36 respondents, and data were analyzed using SmartPLS 4. The results show that managerial competence and information technology utilization do not have a significant effect on accountability, while internal control systems have a positive and significant effect. Community participation does not moderate the relationships among these variables. This study recommends strengthening internal control systems, enhancing the technical competence of village officials, and empowering communities to encourage greater participation in supervising village fund management.